SARS‐CoV‐2 structural coverage map reveals viral protein assembly, mimicry, and hijacking mechanisms. Issue 9 (14th September 2021) - O'Donoghue, Seán I; Schafferhans, Andrea; Sikta, Neblina; Stolte, Christian; Kaur, Sandeep; Ho, Bosco K; Anderson, Stuart; Procter, James B; Dallago, Christian; Bordin, Nicola; Adcock, Matt; Rost, Burkhard
Abstract: We modeled 3D structures of all SARS‐CoV‐2 proteins, generating 2, 060 models that span 69% of the viral proteome and provide details not available elsewhere. We found that ˜6% of the proteome mimicked human proteins, while ˜7% was implicated in hijacking mechanisms that reverse post‐translational modifications, block host translation, and disable host defenses; a further ˜29% self‐assembled into heteromeric states that provided insight into how the viral replication and translation complex forms. To make these 3D models more accessible, we devised a structural coverage map, a novel visualization method to show what is—and is not—known about the 3D structure of the viral proteome. We integrated the coverage map into an accompanying online resource (https://aquaria.ws/covid ) that can be used to find and explore models corresponding to the 79 structural states identified in this work. The resulting Aquaria‐COVID resource helps scientists use emerging structural data to understand the mechanisms underlying coronavirus infection and draws attention to the 31% of the viral proteome that remains structurally unknown or dark. SYNOPSIS: 2, 060 structural models spanning 69% of the SARS‐CoV‐2 proteome are generated and presented in a novel visual layout that summarises current knowledge on viral protein structures, and provides insight into viral replication, mimicry, and hijacking. 2, 060 structural models spanning 69% of the SARS‐CoV‐2 proteome are built, grouped in 79 states and visualized in a concise structural coverage map. ˜6% of the viral proteome appears to mimic human proteins, with the strongest evidence seen for mimicry of three human helicases (UPF1, IGHMBP2, and AQR) by the viral helicase NSP13. ˜7% of the viral proteome is implicated in hijacking human proteins, thereby reversing post‐translational modifications, blocking host translation, and disabling host defenses. ˜29% of the viral proteome self‐assembles into heteromers, with the heteromeric states suggesting the order in which proteins assemble to form the replication and translation complex. Abstract : 2, 060 structural models spanning 69% of the SARS‐CoV‐2 proteome are generated and presented in a novel visual layout that summarises current knowledge on viral protein structures, and provides insight into viral replication, mimicry, and hijacking.